Reduced Sink Activity in Growing Shoot Tissues of Maize under Salt Stress of the First Phase may be Compensated by Increased PEP‐Carboxylase Activity. (9th February 2016) - Hütsch, B. W.; Osthushenrich, T.; Faust, F.; Kumar, A.; Schubert, S.
Abstract: The effects of salt stress (100 mm NaCl for 6 days) on growing tissues (shoot apex, growing leaf segments, root tips) of young maize plants ( Zea mays L. cv. Pioneer 3906) were investigated in comparison to an unsalinized control, focusing on assimilate supply from source leaves and the activity of sucrolytic enzymes in the sink tissues. The objectives were to test whether (i) phloem unloading in growing tissues is mainly symplastic, (ii) salinity reduces sink activity, determined either as sucrose synthase activity (indicator for the symplastic pathway) or as acid invertase activity (indicator for the apoplastic pathway), and (iii) PEP‐carboxylase activity is increased under salinity to compensate for reduced sink activity. For growing tissues of young maize shoots, it can be assumed that phloem transport of sucrose is mainly driven by symplastic unloading into the sink cells. In maize root tips, both, apoplastic and symplastic pathways, contributed to carbohydrate supply to the sink cells. The activity of acid invertase in growing shoot tissues was very low, and the alkaline invertase contributed less than 10 % to the cytoplasmic sucrolytic activity. Salt stress of the first phase (mainly osmotic stress) caused a significant inhibition of acid invertase activity in the growing leaf segments and in the root tips, which was also true for alkaline invertase activity in the root tips as well as for sucrose synthase activity in root tips and shoot apex. The decrease of sucrose synthase activity in shoot apex might be particularly detrimental for the plant growth, as this tissue with a high cell division rate relied entirely on cytoplasmic enzyme activities. Under salt stress, PEP carboxylase activity was significantly increased in growing leaves and the shoot apex of maize, whereas no significant effect was observed in the root apex. In conclusion, PEP carboxylase can have an anaplerotic function supporting the demand for metabolites in growing shoot tissues of young maize plants under salt stress. In root tips, an additional supply of organic acids to the tricarboxylic acid cycle is probably not needed, as sucrolytic sink activity, which was high even under saline conditions, can meet the demand of the sink cells.